Determinants of land use change: evidence from a community study in Honduras - Bergeron, Gilles; Pender, John L. (International Food Policy Research Institute, 1999)
This study investigates the micro-determinants of land use change using community, household and plot histories, an ethnographic method that constructs panel data from systematic oral recalls. A 20-year historical timeline (1975-1995) is constructed for the village of La Lima in central Honduras, based on a random sample of 97 plots. Changes in land use are examined using transition analysis and multinomial logit analysis. Transition analysis shows that land use transitions were relatively infrequent in areas under extensive cultivation, but more so in areas of intensive cultivation; and that most changes favored intensification. Econometric analysis suggests that land use intensification was influenced by plot level variables (especially altitude, slope, distance to a road and tenure), farm level variables (human capital, farm size, and ownership of productive implements), and by community variables (especially presence of technical assistance programs).To the extent these results are found to be more broadly representative, they suggest that there may be good potential to promote income-enhancing horticultural development through investments in technical assistance and education in similar communities elsewhere in Honduras. The study concludes that the plot history approach is a potentially valuable tool for investigating the underlying causes of change in land use at the micro-level. The method is particularly well adapted to situations where the availability of data is poor. It is also suggested that the approach would have additional benefits when replicated over a large number of sites as this would allow integration of higher order determinants (e.g. national policies and market incentives) while expanding the applicability and representativity of findings.